PRESCRIPTION OF ANTIBIOTICS FROM ACCESS GROUP ACCORDING TO AWARE CLASSIFICATION: DATA FROM COMMUNITY PHARMACIES IN SLEMAN REGENCY YOGYAKARTA - Sinatria, Arifi Bhakti; Harun, Sabariah Noor; Saepudin (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Antibiotic resistance is the most challenging problem in the 21st century. Therefore, the WHO released a classification of antibiotics into the Access, Watch, and Reserve (AWaRe) group, with the aim of optimizing the use of the access group to at least 60%. The objective of this study was to determine the profile of antibiotic prescriptions at community pharmacies in Sleman Regency, Yogyakarta, during the period 2019–2022, based on the AWaRe classification. A Cross-sectional survey was designed to collect data on antibiotic prescriptions from community pharmacies across four regions of the Sleman Regency. Each antibiotic was classified in accordance with the AWaRe classification and the quantity of prescribed antibiotics was calculated in DDD units following the ATC/DDD method. This study found that in terms of the antibiotic agents, 10-13 antibiotic from the Access group (52%–62%) were prescribed during the study period. Meanwhile, in terms of quantity expressed in DDD units, 52.38% and 61.90% of prescribed antibiotics were from the Access group, according to the AWaRe classification released by the WHO and the Indonesian Ministry of Health, respectively. In conclusion, antibiotic prescriptions at community pharmacies in Sleman Regency, Yogyakarta, have reached the target of optimizing the use of access groups according to the Indonesian Ministry of Health, but were still slightly below the target of the WHO. eywords: Antibiotic Prescription; ATC/DDD; AWaRe Classification; Community Pharmacy